Predicting seasonal infection of eyeworm (Oxyspirura petrowi) and caecal worm (Aulonocephalus pennula) in northern bobwhite quail (Colinus virginianus) of the Rolling Plains Ecoregion of Texas, USA. (April 2019) - Blanchard, Kendall R.; Kalyanasundaram, Aravindan; Henry, Cassandra; Brym, Matthew Z.; Surles, James G.; Kendall, Ronald J.
Abstract: The northern bobwhite quail ( Colinus virginianus ) is a popular gamebird in the Rolling Plains Ecoregion of West Texas. However, there has been a population decline in this area over recent decades. Consistent reports indicate a high prevalence of the eyeworm ( Oxyspirura petrowi ) and caecal worm ( Aulonocephalus pennula ), which may be of major influence on the bobwhite population. While research has suggested pathological consequences and genetic relatedness to other pathologically significant parasites, little is known about the influence of climate on these parasites. In this study, we examined whether seasonal temperature and precipitation influences the intensity of these parasites in bobwhite. We also analyzed quantitative PCR results for bobwhite feces and cloacal swabs against temperature and precipitation to identify climatic impacts on parasite reproduction in this region. Multiple linear regression analyses were used for parasite intensity investigation while binary logistic regression analyses were used for parasite reproduction studies. Our analyses suggest that caecal worm intensity, caecal worm reproduction, and eyeworm reproduction are influenced by temperature and precipitation. Temperature data was collected 15, 30, and 60 days prior to the date of collection of individual bobwhite and compared to qPCR results to generate a temperature range that may influence future eyeworm reproduction. This is the first preliminary study investigating climatic influences with predictive statistics on eyeworm and caecal worm infection of northern bobwhite in the Rolling Plains. Graphical abstract: Image 1 Highlights: Bobwhite quail in West Texas, USA have high prevalence of eyeworm and caecal worm. Wild quail were necropsied and fecal samples collected. Parasite intensity and reproduction from this data compared to climate data of study location. Caecal worm intensity, reproduction, and eyeworm reproduction influenced by climate. Eyeworm reproduction influenced by temperature 60 days prior to bobwhite collection.